ANALISIS KNOWLEDGE SHARING TERHADAP KINERJA UKM BERBASIS SIKAP KEWIRAUSAHAAN DI KOTA BANJARMASIN - Isra Ul Huda; Anthonius Junianto Karsudjono (Al-Kalam Jurnal Komunikasi, Manajemen dan Bisnis, 2023)
This study aims to determine and also analyze the effect of knowledge sharing onentrepreneurial attitudes and also the performance of SMEs in the city of Banjarmasin. This study uses quantitative data analysis methods, the sample in this study is SMEs in the city of Banjarmasin which are divided into 10 people in each sub-district with a total of 50 respondents. PLS analysis tool. The results of the analysis carried out prove that knowledge sharing has a direct, positive and significant effect on entrepreneurial attitudes and also the performance of SMEs in the city of Banjarmasin. Then the entrepreneurial attitude has a direct, positive and significant influence on the performance of SMEs in the city of Banjarmasin. This study also proves that there is an indirect, positive and significant effect between the performance of SMEs in the city of Banjarmasin through entrepreneurial attitudes.